Application of the Aras Method in Problem Completion of Determining the Location of New Student Admission - Prind Triajeng Pungkasanti; Henny Indriyawati; Susanto Susanto (Universitas Kristen Satya Wacana, 2022)
During the screening of new students, each state and private institution is required to carry out promotion in order to obtain the number of students according to the predetermined target. Problems that often occur when determining the location of promotion, the New Student Admission Team (PMB) determine the location of promotions randomly without considering several factors that can affect the number of students who will join. This is often done mainly by private university such as Semarang University (USM). To overcome this, a system is needed to provide information for the New Student Admission Team (PMB) in making decisions on the location of USM promotions. This system applies the Additive Ratio Assessment (ARAS) method and criteria that can affect the number of students who will later register because the determination of the location of the promotion is right on target. Criteria and weights include: Distance (cost) with a weight of 30%, number of students (benefit) with a weight of 40%, school status (benefit) with a weight of 20%, and a source of information (benefit) with a weight of 10%. The programming language used by PHP and data bases uses MySQL. The final result of this study is a decision support system that can provide information to the PMB team about the location of the school that has the potential for USM promotion.